2018
DOI: 10.1186/s13020-018-0189-6
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effect of scalp acupuncture on natal autism and regressive autism

Abstract: BackgroundAutism spectrum disorders (ASD) is a common disease and the incidence has been rising constantly. Acupuncture is one of the most widely used complementary and alternative medicine therapies. Despite studies had been done on the effectiveness of acupuncture on ASD children, how factors such as chronological age and the onset pattern influence the effectiveness of the therapy remains unclear. The aim of this retrospective study is to know how symptomatology of ASD alters upon the introduction of scalp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…[ 22 ] As a major form of Chinese medicine, from clinical trials and SRs, acupuncture is reported to improve various developmental and behavioral aspects of children with ASD, it's safe but children experienced pain and cried during the treatment. [ 23 26 ] Tetrahydrobiopterin is an important cofactor in the biosynthesis of catecholamines and serotonin, and in the treatment of ASD, it is reported to significantly improve social interaction subscale of the CARS. [ 27 ] l -Carnosine is a dipeptide known for its antioxidant properties and proposed enhancement of γ-aminobutyric acid function in the brain, with possible anticonvulsive effects, it was showed to significantly improve CARS score on ASD children.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] As a major form of Chinese medicine, from clinical trials and SRs, acupuncture is reported to improve various developmental and behavioral aspects of children with ASD, it's safe but children experienced pain and cried during the treatment. [ 23 26 ] Tetrahydrobiopterin is an important cofactor in the biosynthesis of catecholamines and serotonin, and in the treatment of ASD, it is reported to significantly improve social interaction subscale of the CARS. [ 27 ] l -Carnosine is a dipeptide known for its antioxidant properties and proposed enhancement of γ-aminobutyric acid function in the brain, with possible anticonvulsive effects, it was showed to significantly improve CARS score on ASD children.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study found that the therapeutic effectiveness of SAT decreases with increasing age. [33] One of the trials even suggests that rehabilitation efficacy is improved by retaining the needle on the scalp while training. [20] The effect of age on the efficacy of SAT requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…The early intervention service (EIS) for children with developmental delay has been a booming welfare issue in Taiwan in recent years [44]. Acupuncture for diseases such as cerebral palsy [27, 45] and autism spectrum disorder (ASD) [46] plus rehabilitation training have been widely used for children with developmental delay due to the therapeutic effectiveness. In children with cerebral palsy, acupuncture plus rehabilitation training improved gross motor function, reduced muscle spasms, and enhanced daily life activities [45].…”
Section: Discussionmentioning
confidence: 99%
“…In children with cerebral palsy, acupuncture plus rehabilitation training improved gross motor function, reduced muscle spasms, and enhanced daily life activities [45]. Several reviews also suggested that acupuncture may be an effective treatment for alleviating the symptomatology of ASD [46, 47]. Acupuncture also showed some promise for other mental and neurological diseases, such as anxiety [48], nocturnal enuresis [49] and visual impairment [50, 51].…”
Section: Discussionmentioning
confidence: 99%